Pengaruh Ukuran Bank dan Loan to Assets Ratio serta Suku Bunga terhadap Kredit Bermasalah pada Bank yang Terdaftar di BEI Periode 2010-2015 - Sukma Wati; F. Defung; M. Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This study aims to analyze the effect of Company Size, Loan to Asset Ratio (LAR) and Interest Rate to Non Performing Loans at banks registered at Indonesia Stock Exchange. The dependent variable in this study are Non Performing Loans and independent variables in this study are bank size, Loan to Asset Ratio and Interest Rate. The population in this research is 43 banks of Private National Private Bank in Indonesia period 2010-2015. The sampling technique used Purposive Sampling method and obtained as many as 19 National Private Banks. The method of analysis used is Panel Data Regression Analysis.The results of this study indicate that the size of the Bank has a positive but not significant effect on Non Performing Loans, Loan to Asset Ratio has a negative and significant effect on Non Performing Loans. And Interest Rates have positive but not significant effect on Non Performing Loans.